English as a Medium of Instruction: Exploring Benefits and Challenges in the 21st Century - Rachid Elkhayma (Masyarakat Linguistik Indonesia Universitas Andalas, 2022)
Language education has remarkably undergone a major shift since the advent of the communicative approach in the 1970s. As English has long become the world’s lingua franca, the approach to its teaching and learning has also witnessed an outstanding breakthrough. This is illustrated by the growing figures of non-native English language speakers that far exceed the native ones, and that entails a special status for English. Therefore, different proposals have been made as to how English should best be approached in teaching given its various characteristics as an international language for communication. One of these approaches is English as a medium of instruction (EMI). In this regard, and in their attempt to attain internationalization and develop the quality of higher education, many institutions in non-English speaking countries (e.g., Japan, China, Malaysia, Germany, etc.) have opted for the world’s first language as a means of instruction in various academic subjects, namely the science-related ones. This paper, then, is set to conceptualize and highlight the process of using English as a language of teaching and learning at the tertiary level, and explores its potential benefits and challenges for students and professors in the Moroccan higher educational context.